From the desk of the dean : the history and future of arts and sciences education - Fitzpatrick, Mary Anne; Say, Elizabeth A.; Mason, Sally (University of South Carolina Press, 2017)
"For those who have devoted their lives to teaching, learning, and innovation in the arts and sciences, it likely comes as no surprise that there has been a revaluing and devaluing of the work of students and faculty in the arts and sciences fields. In response Mary Anne Fitzpatrick and Elizabeth A. Say offer From the Desk of the Dean, an anthology of original essays by arts and sciences deans and former deans addressing the increasing demands for vocational education at the expense of the liberal arts and sciences. This informative collection examines the challenges in higher education and offers a compelling case for the value of the liberal arts and sciences. To honor the fiftieth anniversary of the founding of the Council of Colleges of Arts and Sciences (CCAS), the largest association of arts and sciences deans in the country, editors Fitzpatrick and Say, both past presidents of CCAS, have assembled nine essays as well as three section introductions to create From the Desk of the Dean. Their goal is to prompt open discussions about American higher education and the perceived value of degrees in the basic arts and science fields. Many agree that to the public an accounting degree is of greater value than an art history degree and a civil engineering degree has more value than a degree in physics. The contributors to the volume include deans with experience working at public and private universities, large research universities, comprehensive teaching institutions, as well as scholarly and advocacy groups. Their essays, informed by their experiences as leaders who support excellence in teaching, research, and creative activity in the basic fields of human knowledge, examine the many criticisms of higher education and of the faculty and programs in arts and sciences"--